2013
DOI: 10.1016/j.freeradbiomed.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine DNA glycosylase-1 links DNA repair to cellular signaling via the activation of the small GTPase Rac1

Abstract: 8-Oxo-7,8-dihydroguanine (8-oxoG) is one of the most abundant DNA base lesions induced by reactive oxygen species (ROS). Accumulation of 8-oxoG in the mammalian genome is considered a marker of oxidative stress, to be causally linked to inflammation, and is thought to contribute to aging processes and various aging-related diseases. Unexpectedly, mice that lack 8-oxoguanine DNA glycosylase-1 (OGG1) activity and accumulate 8-oxoG in their genome have a normal phenotype and longevity; in fact, they show increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 61 publications
7
72
0
3
Order By: Relevance
“…6B). Similarly, NOX4 was proposed to localize to the nuclear membrane in alveolar epithelial cell A549 (47). We have also shown that p22 phox localizes to the nuclear membrane (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…6B). Similarly, NOX4 was proposed to localize to the nuclear membrane in alveolar epithelial cell A549 (47). We have also shown that p22 phox localizes to the nuclear membrane (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…As compared with wild-type neuronal stem cells, loss of plasticity toward a terminally differentiated astrocytic lineage occurs in Ogg1-deficient neuronal stem cells that accumulate mtDNA damage (58). Ogg1 also has an emerging important role in linking DNA repair to Rac1 and Ras cellular signaling pathways (59,60). These findings support the notion that defects in Ogg1 and 8-oxoG DNA repair play an important role in enhancing mtDNA damage.…”
Section: Discussionsupporting
confidence: 56%
“…In mammals, the intra-helical 8-oxoG is recognized and excised by the E. coli Fpg homolog 8-oxoguanine DNA glycosylase 1 (OGG1) from nuclear and mitochondrial genome during base excision repair processes [19,20]. The resulting free 8-oxoG base is capable of binding to OGG1 with high affinity, and the complex then functions as an activator of Ras and Rho family GTPases contributing to oxidative stress related cellular responses [21][22][23]. Here, our aim was to investigate the consequence if 8-oxoG is not removed from mtDNA and the oxidatively modified mtDNA is released from the cells.…”
Section: Introductionmentioning
confidence: 99%